THE USE OF ONLINE ENCYCLOPEDIA TO DEVELOP STUDENTS’ READING COMPREHENSION ON DESCRIPTIVE TEXT - Abriana, Koradwitya; Salam, Urai; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: The purpose of this research is to investigate the effectiveness of the use of online encyclopedia on factmonster.com to develop students’ reading comprehension on descriptive text. This research was conducted as pre experimental design. The researcher took XI IPA class of SMAN 2 Sungai Ambawang in academic year 2012/2013 as the sample. The data were derived from multiple choice tests that were taken from a student’s book. The result showed that the mean score of pretest was 49.00 while the posttest was 65.31. The different score between pretest and posttest was 16.31. The students’ development in using online encyclopedia especially on factmonster.com during the research showed a good change. It was found from the result of t-test that t-value is higher than t-table (5.22 > 2.048). In conclusion, the use of online encyclopedia on factmonster.com is effective to develop the students’ reading comprehension achievement on the descriptive text. Keywords : Descriptive Text, Reading Comprehension, Online Encyclopedia Abstrak : Penelitian ini bertujuan untuk menyelidiki keefektifan penggunaan media enslikopedia online pada situs factmonster.com dalam mengembangkan kemampuan komprehensi membaca siswa pada teks deskriptif. Metode yang digunakan untuk mengumpulkan data adalah Pre-Experimental. Peneliti mengambil kelas XI IPA dari SMAN 2 Sungai Ambawang tahun ajaran 2012/2013 sebagai sampel. Soal pilihan ganda diambil dari buku pegangan siswa. Berdasarkan penelitian, hasil nilai rata-rata pre test siswa adalah 49, sementara nilai rata-rata post test menunjukan 65.31. Dengan demikian dapat dilihat bahwa jarak interval nilai pre test dan post test adalah 16.31. Pengembangan komprehensi membaca siswa dalam penggunaan media enslikopedia online pada situs factmonster.com selama penelitian menunjukan perubahan yg baik. Hal itu dapat dilihat darin hasil penghitungan t-test yg menunjukan bahwa hasil t-test lebih tinggi dari t-table (5.22 > 2.048). Jadi, dapat disimpulkan bahwa penggunaan media enslikopedia online pada situs factmonster.com efektif dalam mengembangkan kemampuan komprehensi membaca siswa pada teks deskriptif. Kata Kunci : Teks Deskriptif, Komprehensi Membaca, Enslikopedia Online